Communication Power - Castells, Manuel 1942- (Oxford Oxford University Press, 2013)
We live in the midst of a revolution in communication technologies that affects the way in which people feel, think, and behave. The media have become the space where power strategies are played out. In the current technological context mass communication goes beyond traditional media and includes the Internet and mobile communication. In this wide-ranging and powerful book, Manuel Castells analyses the transformation of the global media industry by this revolution in communication technologies. He argues that a new communication system, mass self-communication, has emerged, and power relation
Keywords: Comunicación; Poder (Ciencias sociales); Comunicación y tecnología